A review of incidence and mortality of colorectal, lung, liver, thyroid, and bladder cancers in Iran and compared to other countries - Farhood, Bagher; Raei, Behzad; Malekzadeh, Reza; Shirvani, Maryam; Najafi, Masoud; Mortezazadeh, Tohid (Contemporary Oncology/Współczesna Onkologia, 2019)
In Iran, a developing country in southwest Asia, an epidemiologic transition is underway from communicable to noncommunicable diseases. In Iran, cancer is the second largest group of chronic non-communicable diseases (NCDs) and the third most common cause of death following heart disease, accidents and other natural phenomena. There are some studies reporting an increasing trend in the incidence and mortality rate of a variety of cancers in Iran. Therefore, controlling and preventive interventions pertaining to cancers must be a main priority for health policy and it is recommended that the high-risk population receive earlier screening. In this review, incidence and mortality of colorectal, lung, liver, thyroid, and bladder cancers in Iran are reported.